Techno-Economic and Environmental Feasibility Study of a Hybrid Photovoltaic Electrification System in Back-up Mode : A Case Report - Latifath Inoussa; Basile Bruno Kounouhewa; Henri Wilfried Hounkpatin; Hagninou Elagnon Venance Donnou; Victorin Kouamy Chegnimonhan (International Journal of Renewable Energy Development, 2023)
In developing countries, institutions that have to operate continuously during daylight hours consume relatively large amounts of electrical energy for lighting and air conditioning, leading to high bills. Untimely power cuts lead to a fluctuation in the voltage delivered by the conventional network, which induces the malfunctioning of electrical equipment and the discontinuity of judicial work. The use of photovoltaic solar energy makes it possible, on the one hand, to ensure continuity of service in the event of damage, and on the other hand to stem greenhouse gas emissions through the sustainable nature of this energy.  Solar installations also make it possible to maintain the permanent power supply in the event of instability of the electrical network and to correct the voltage variations undergone by the energy equipment. Thus, this  (case) study  is based on the energy balances evaluated on the buildings of the jurisdiction of the city of Kandi (Benin) to propose effective solutions of electrification according to six (6) technical scenarii. Each component of the back up system has been sized considering technical requirements and an economic and environmental study has been carried out. The results indicate that the integrated scenario 6 of a "back-up" system with a solar fraction of up to 37% (49.5 kWc) seems to be the most suitable conf iguration for the current needs of the Kandi jurisdiction due to the shortest time to return on investment (5.1 years) and the maximum annual savings generated (33,674 USD). The environmental impact study has made it possible to determine the CO2  emissions avoided as well as the contribution of Carbon credits that this jurisdiction would reap has been evaluated at 115.8 tCO2  equivalent, or 10.6 hectares of forest carbon preserved over the life of the project. This configuration is therefore strongly recommended for a sustainable energy mix in the jurisdictions of Benin as well as for administrative or similar sites where electricity consumption is maximum during the day.